One-carbon metabolism in methanogenic bacteria: analysis of short-term fixation products of 14CO2 and 14CH3OH incorporated into whole cells. - Daniels, L (1978)
Methanobacterium thermoautotrophicum, M. ruminantium, and Methanosarcina barkeri were labeled with 14CO2 (14CO2 + H14CO3- + 14CO32-) for from 2 to 45 s. Radioactivity was recovered in coenzyme M derivatives, alanine, aspartate, glutamate, and several unidentified compounds. The properties of one important structurally unidentified intermediate (yellow fluorescent compound) displayed UV absorbance maxima at pH 1 of 290 and 335 nm, no absorbance in the visible region, and a fluorescence maximum at 460 nm. Label did not appear in organic phosphates until after 1 min. 14CH3OH was converted by M. barkeri primarily into coenzyme M derivatives at 25 s. [2-14C]acetate was assimilated by M. thermoautotrophicum mainly into alanine and succinate during 2 to 240 s, but not into coenzyme M derivatives or yellow fluorescent compound. Cell-free extracts of M. thermoautotrophicum lacked ribulose 1,5-bisphosphate carboxylase activity. The data indicated the absence of the Calvin, serine, and hexulose phosphate paths of C1 assimilation in the methanogens examined and indicated that pyruvate was an early intermediate product of net CO2 fixation. The in vivo importance of coenzyme M derivatives in methanogenesis was demonstrated.